miR-21, miR-106b and miR-375 as Novel Potential Biomarkers for Laryngeal Squamous Cell Carcinoma - Yu, Xing; Wu, Yibo; Liu, Yang; Deng, Hongxia; Shen, Zhisen; Xiao, Bingxiu; Guo, Junming (Current Pharmaceutical Biotechnology, 2014)
MicroRNAs (miRNAs), the endogenous noncoding RNAs, are involved in carcinogenesis. Laryngeal squamous cell carcinoma (LSCC) is the common cancer in head and neck. Whether miRNAs can be used in the diagnosis of LSCC is largely unknown. The purpose of this study was to identify whether miRNAs could be use as potential biomarkers for LSCC diagnosis. The expression levels of miR-21, miR-106b and miR-375, in LSCC tissues and paired nontumor tissues were first quantitatively analyzed by reverse transcription-polymerase chain reaction. Then, the relationships between their expression levels and clinicopathological parameters of patients with LSCC were further determined. We found that these miRNAs’ expression levels were significantly different between LSCC tissues and adjacent normal tissues. Two miRNAs, miR-21 and miR-106b were found up-regulated in cancer tissues (P=0.0012 and P<0.001, respectively), while miR-375 down-regulated (P<0.001). Moreover, miR-21 and miR-106b levels were found significantly increased in poorly (G3)/moderately differentiated (G2) cancer tissues comparing with well differentiated (G1) and dysplasia (D) tissues (P<0.001, respectively). Their levels were also positively associated with lymph node metastasis (P<0.05) and TNM stages (P<0.01). However, miR-375 expression level was only found negatively associated with TNM stages. Our preliminary data suggest that three miRNAs, miR-21, miR-106b and miR- 375 might become novel tumor markers for LSCC diagnosis.
Keywords: MiR-106b